N6-methyladenosine RNA modified BAIAP2L2 facilitates extracellular vesicles-mediated chemoresistance transmission in gastric cancer - Yuhan Liao; Xinhua Chen; Hao Xu; Yunfei Zhi; Xinghua Zhuo; Jiang Yu; Liang Zhao (Journal of Translational Medicine)
Abstract Background Extracellular vesicles (EVs) produced in the tumor microenvironment in response to chemotherapy promote chemotherapy-resistant phenotypes. However, the role of EVs proteins induced by gastric cancer (GC) cell chemotherapy in regulating chemotherapy resistance remains unclear. Methods Immunohistochemistry was used to verify the relationship between brain-specific angiogenesis inhibitor 1-associated protein-2-like protein 2 (BAIAP2L2) expression and chemotherapy resistance in advanced GC. The relationship between BAIAP2L2 and chemotherapy resistance was verified using a subcutaneous tumor model in nude mice. Transmission electron microscopy, nanoparticle tracking analysis, and western blotting were performed to detect purified EVs. Tandem mass tag (TMT) analysis was used to detect differential labels. The interaction between YTH domain-containing family protein1 (YTHDF1) and BAIAP2L2 in GC cells was confirmed by RIP-qPCR analysis using a YTHDF1-specific antibody. Results We found that BAIAP2L2 was associated with chemotherapy resistance to GC in clinical samples and was increased in chemotherapy-resistant GC cells. Mechanistically, BAIAP2L2 promotes the transfer of chemotherapy resistance from resistant GC cells to sensitive cells through EVs proteins, such as ANXA4. Furthermore, ANXA4 promoted platinum-based chemical resistance in GC by mediating autophagy. Interestingly, YTHDF1 facilitates the translation of BAIAP2L2 and ANXA4 through m6A modifications. Conclusions Our findings reveal the key role of BAIAP2L2 as a potential prognostic marker and therapeutic target for chemotherapy resistance in GC.